Acanthobdella peledina Grube 1851 ... - Carle, Danielle Božena De; Gajda, Łukasz; Bielecki, Aleksander; Cios, Stanisław; Cichocka, Joanna M.; Golden, Heidi E.; Gryska, Andrew D.; Sokolov, Sergey; Shedko, Marina Borisowna; Knudsen, Rune; Utevsky, Serge; Świątek, Piotr; et al. (Zenodo, 2022)
POPULATIONS OF A. PELEDINA The present evidence suggests that A. peledina from Alaska is distinct, to some degree, from European samples. However, Siberia and the Russian Far East have not been adequately sampled genetically for A. peledina . Accordingly, it is difficult to determine the genetic variability and population structuring of this species. Coupled with increased taxon sampling, additional genetic sampling of Alaskan populations could help to indicate whether they are a unique species or population. Sampling of quickly evolving nuclear loci or, ideally, next generation sequence data (e.g. RADSeq) would be useful for determining whether gene flow exists between the Alaskan and Nordic localities. Unfortunately, COI , the most common marker for determining differences between leech species and populations (de Carle et al. , 2017; Tessler et al. , 2018c; Mack et al. , 2019), and additional nuclear loci did not amplify for these samples, potentially leading to some issues with missing data. Furthermore, ... : Published as part of Carle, Danielle Božena De, Gajda, Łukasz, Bielecki, Aleksander, Cios, Stanisław, Cichocka, Joanna M., Golden, Heidi E., Gryska, Andrew D., Sokolov, Sergey, Shedko, Marina Borisowna, Knudsen, Rune, Utevsky, Serge, Świątek, Piotr & Tessler, Michael, 2022, Recent evolution of ancient Arctic leech relatives: systematics of Acanthobdellida, pp. 149-168 in Zoological Journal of the Linnean Society 196 on pages 165-166, DOI: 10.1093/zoolinnean/zlac006, http://zenodo.org/record/7037718 ...